Weather Information for Garden City, 2018 - J. Elliott (Kansas Agricultural Experiment Station Research Reports, 2019)
Summary of 2018 weather for research conducted at the Garden City field location.
Keywords: Garden City weather; 2018 weather; southwest Kansas weather report